Reading Literature in the Time of Pandemic - Betty Sianturi (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2020)
This paper contextualizes the role of literature during the current state of Covid-19 outbreak. As representation of plague has been a stable in literature across time and space, reading literature about pandemic offers important insights in dealing with the changing period. This study offers a reading of ‘The Marque of Red Death’, a short story written by Edgar Allan Poe which dramatizes the outbreak of titular plague. Poe’s narration contextualizes the horrifying aspects of plague and also criticizes the social inequality concerning the ability of different social classes to cope with pandemic. Hence, this depiction asserts that ecological problem is inseparable with social problem and racial inequality. This study is conducted under ecocritical framework which emphasizes the reorientation of human and non-human relationship through the imaginary literature. The findings suggest that the non-human entity in form of plague is depicted as a disruptive force that abolish the progress of human civilization. This dramatization explores humanity to ponder their position in the world as a reminder of their mortality. The analysis suggests that during the troubled era of Covid-19 outbreak, reading representation of plague in literature can provide an idea with how people across time and space cope with pandemic outbreak.